Zebrafish irritant responses to wildland fire-related biomass smoke are influenced by fuel type, combustion phase, and byproduct chemistry. Issue 16 (18th August 2021) - Martin, W. Kyle; Padilla, S; Kim, YH; Hunter, DL; Hays, MD; DeMarini, DM; Hazari, MS; Gilmour, MI; Farraj, AK
ABSTRACT: Human exposure to wildfire-derived particulate matter (PM) is linked to adverse health outcomes; however, little is known regarding the influence of biomass fuel type and burn conditions on toxicity. The aim of this study was to assess the irritant potential of extractable organic material (EOM) of biomass smoke condensates from five fuels (eucalyptus, pine, pine needle, peat, or red oak), representing various fire-prone regions of the USA, burned at two temperatures each [flaming (approximately 640°C) or (smoldering approximately 500°C)] using a locomotor assay in zebrafish ( Danio rerio ) larvae. It was postulated that locomotor responses, as measures of irritant effects, might be dependent upon fuel type and burn conditions and that these differences relate to combustion byproduct chemistry. To test this, locomotor activity was tracked for 60 min in 6-day-old zebrafish larvae (25–32/group) immediately after exposure to 0.4% dimethyl sulfoxide (DMSO) vehicle or EOM from the biomass smoke condensates (0.3–30 µg EOM/ml; half-log intervals). All EOM samples produced concentration-dependent irritant responses. Linear regression analysis to derive rank-order potency indicated that on a µg PM basis, flaming pine and eucalyptus were the most irritating. In contrast, on an emission-factor basis, which normalizes responses to the amount of PM produced/kg of fuel burned, smoldering smoke condensates induced greater irritant responses (>100-fold) than flaming smoke condensates, with smoldering pine being the most potent. Importantly, irritant responses significantly correlated with polycyclic aromatic hydrocarbon (PAH) content, but not with organic carbon or methoxyphenols. Data indicate that fuel type and burn condition influence the quantity and chemical composition of PM as well as toxicity.